Waterborne Polyurethane Colloids with Sensitive CO2‐Switchable Hydrophilic/Hydrophobic Properties. Issue 17 (1st August 2018) - Shieh, Yeong‐Tarng; Zeng, Zi‐Hau; Cheng, Chih‐Chia
Abstract: A novel conceptual approach to gas‐responsive functionality, with the capability to tune the amphiphilic characteristics of existing waterborne polyurethanes (WPUs), via CO2 /N2 bubbling in aqueous solution, is exploited. In this study, a series of functional WPUs are successfully prepared. These colloids exhibit high aqueous stability, excellent capability for emulsification/demulsification as a surfactant, and reversible hydrophilic/hydrophobic phase transition owing to reversible formation of carboxylic acid moieties induced by bubbling CO2 gas. More interestingly, when carboxylated multiwalled carbon nanotubes (CNTs) are covalently incorporated into these WPUs, the CNT exhibits CO2 ‐switchable amphiphilic behavior in a two‐phase mixture of n ‐butanol (BuOH)/deionized water, forming a stable hydrophobic CNT dispersion in BuOH upon CO2 bubbling, and reversibly reverting to the previous hydrophilic CNT dispersion in water upon N2 bubbling. With simple preparation and switchable amphiphilic properties, these CO2 ‐responsive WPUs offer a paradigm for the development of multifunctional gas‐responsive polymers. Abstract : CO2 ‐responsive CNT‐incorporated waterborne polyurethanes in a two‐phase solution can form a stable dispersion in the n ‐butanol phase and then revert to the water phase by the simple addition/removal of CO2 .